“Early Psychosis” as a mirror of biologist controversies in post-war German, Anglo-Saxon, and Soviet Psychiatry† - Rzesnitzek, Lara (Frontiers in Psychology, 2013)
The English term ‘early psychosis’ was coined in the 1930s to refer to feelings of irritability, loss of concentration, hypochondriac ideas, moodiness and lassitude that were seen to precede the onset of clear-cut hallucinations and delusions. The history of thinking about ‘early psychosis’ under names such as ‘latent’, ‘masked’, ‘mild’, ‘simple’ or ‘sluggish’ schizophrenia before World War II and afterwards on the different sides of the Wall and the Iron Curtain reveals ‘early psychosis’ as a mirror of quite aged international biologist controversies that are still alive today and to the same extent as they are misunderstood, are influential in their implications in today’s psychiatry.